Detection of HTLV-1 proviral DNA in cell-free DNA: Potential for non-invasive monitoring of Adult T cell leukaemia/lymphoma using liquid biopsy? - Joris, Thomas; Haddow, Jana; Taylor, Graham P.; Cook, Lucy B. M.; Rowan, Aileen G. (Frontiers in Immunology, 2023)
Introduction Fragmented genomic DNA is constitutively released from dying cells into interstitial fluid in healthy tissue. In cancer, this so-called ‘cell-free’ DNA (cfDNA) released from dying malignant cells encodes cancer-associated mutations. Thus, minimally invasive sampling of cfDNA in blood plasma can be used to diagnose, characterise and longitudinally monitor solid tumours at remote sites in the body. 5% of carriers of Human T cell leukaemia virus type 1 (HTLV-1) develop Adult T cell leukaemia/lymphoma (ATL), and a similar percentage develop an inflammatory CNS disease, HTLV-1 associated myelopathy (HAM). In both ATL and HAM, high frequencies of HTLV-1 infected cells are present in the affected tissue: each carrying an integrated DNA copy of the provirus. We hypothesised that turnover of infected cells results in the release of HTLV-1 proviruses in cfDNA, and that analysis of cfDNA from infected cells in HTLV-1 carriers might contain clinically useful information pertaining to inaccessible sites in the body- e.g. for early detection of primary or relapsing localised lymphoma type ATL. To evaluate the feasibility of this approach, we tested for HTLV-1 proviruses in blood plasma cfDNA. Methods CfDNA (from blood plasma) and genomic DNA (gDNA, from peripheral blood mononuclear cells, PBMC) was isolated from blood from 6 uninfected controls, 24 asymptomatic carriers (AC), 21 patients with HAM and 25 patients with ATL. Proviral (HTLV-1 Tax) and human genomic DNA (the beta globin gene, HBB) targets were quantified by qPCR using primer pairs optimised for fragmented DNA. Results Pure, high quality cfDNA was successfully extracted from blood plasma of all study participants. When compared with uninfected controls, HTLV-1 carriers had higher concentrations of cfDNA circulating in their blood plasma. Patients with ATL who were not in remission had the highest levels of blood plasma cfDNA in any group studied. HTLV-1 proviral DNA was detected in 60/70 samples obtained from HTLV-1 carriers. The proviral load (percentage of cells carrying proviruses) was approximately tenfold lower in plasma cfDNA than in PBMC genomic DNA, and there was a strong correlation between the proviral load in cfDNA and PBMC genomic DNA in HTLV-1 carriers that did not have ATL. cfDNA samples in which proviruses were undetectable also had very low proviral load in PBMC genomic DNA. Finally, detection of proviruses in cfDNA of patients with ATL was predictive of clinical status: patients with evolving disease had higher than expected total amount of proviruses detectable in plasma cfDNA. Discussion We demonstrated that (1) HTLV-1 infection is associated with increased levels of blood plasma cfDNA, (2) proviral DNA is released into blood plasma cfDNA in HTLV-1 carriers and (3) proviral burden in cfDNA correlates with clinical status, raising the possibility of developing assays of cfDNA for clinical use in HTLV-1 carriers.